Factors affecting brand loyalty : a study of palm cooking oil in Malaysia - Shaban, Omar Kassim A. (2018)
The reality of competing under globalization has dramatically increased the importance of brand loyalty in the past decades. Majority of the studies on brand loyalty have been conducted in developed countries either from the organizational perspective or from the individual perspective. Studies related to palm oil were mainly from the perspective of health and price. Very few studies have explored the brand loyalty of palm cooking oil. Hence, the primary purpose of this study is to investigate the antecedents of the brand loyalty of palm cooking oil, and enhance the loyalty to palm cooking oil products among its user in Malaysia. A comprehensive framework of palm oil brand loyalty was established based on the Theory of planned behaviour (TPB), Technology Acceptance Model (TAM), Porter Five Forces (PFF), and the Service Quality Model (SQM). A systematic sampling technique was deployed to collect data from the 314 consumers of palm cooking oil in the Klang Valley, Malaysia. Both the Statistical Package for the Social Sciences (SPSS) and AMOS as embedded in structural equation model (SEM) were applied. Confirmatory factor analysis, measurement model and structural model were conducted to test the hypothesis of this study. The results show that: i) perceived usefulness, product quality, product experience, brand commitment and brand awareness had positive effects on attitude and hence behavioural intention; ii) this study also found to have a positive effect on brand loyalty hypotheses. Trust and satisfaction partially mediate the effects of attitude on intention. That is, when consumers of palm oil brand in Malaysia have positive trust and feel satisfied, they will have a positive attitude that will have a positive effect on behavioural intention. iii) The effect of subjective norm on attitude was affected by the moderating effects of the switching cost. The contributions of the study are: i) this study is significant because it contributes to the existing literature by focusing on the factors that affect brand loyalty of palm oil from the customer perspective and the brand perspective; ii) it is important to provide the scientific guidance which helps the decision-makers to understand various implication of brand loyalty of palm oil brand in Malaysia; iii) the study findings could serve as an important basis for researchers and the palm oil industry to understand purchasers’ behavioural intentions and attitude to further formulate strategies to improve the brand loyalty of palm oil.